Codevelopment of life goals and the Big Five personality traits across adulthood and old age - Laura Buchinger; Theresa Margareta Entringer; David Richter; Gert G. Wagner; Denis Gerstorf; Wiebke Bleidorn (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
Since the new millennium, research in the field of personality development has focused on the stability and change of basic personality traits. Motivational aspects of personality and their longitudinal association with basic traits have received comparably little attention. In this preregistered study, we applied bivariate latent growth curve modeling to investigate the codevelopment of nine life goals and the Big Five traits. We tested age, perceived control, gender, educational background, and regional socialization as potential moderators of codevelopment. Data came from the German Socio-Economic Panel study (N = 55,040, age range: 18-103 years) and span a study period of 13 years. During this period, the Big Five traits and life goals were assessed four times. Our findings suggest that development in broader life goal domains (e.g., self-fulfillment) is more strongly connected to personality development across the life span, whereas changes in specific goals (e.g., having children) are more closely tied to trait changes during young and middle adulthood. The strongest codevelopment was found between Openness and agentic goals with a focus on personal growth followed by codevelopment between Agreeableness and communal goals. Developmental stage and educational background moderated the codevelopment of Conscientiousness and economic achievement as well as family-related goals. Contrary to previous research, we found that Neuroticism codeveloped with communal life goals (i.e., having a happy relationship/marriage). Our findings reinforce theoretical frameworks that highlight the role of changing opportunities, constraints, and developmental tasks across adulthood.
Keywords: 330; life goals; Big Five; longitudinal study; lifespan development; corresponsive principle